EVALUASI PELAKSANAAN PROGRAM HOME CARE PADA PUSKESMAS BARA-BARAYA KOTA MAKASSAR - Ma'mur Haswira; Wahidin Wahidin; Syarif Ahmad (Jurnal Administrasi Negara, 2019)
Home care services at midnight many residents complained and there is no distribution of home care officers at the Bara-Baraya Public Health Center in Makassar. The focus of research in this study is the evaluation of the implementation of home care programs at the Bara-Baraya Public Health Center in Makassar City. This study aims to evaluate the implementation of home care programs at the Makassar City of Bara Baraya Health Center. The approach used in this study is a qualitative approach that describes and observes deeply the evaluation of the implementation of home care programs at the Makassar City of Bara Baraya Health Center. This research also uses applied research design. The data source in this study was taken from four home care officers at the Bara-Baraya Public Health Center in Makassar City and four people who use home care services. The results showed that the input sub-variables can be quite good. Medical devices such as thermometers, tensimeters, and stethoscopes function properly and are suitable for use in home care health services. Then operational funds such as staff salaries are paid according to the number of visits to the community. The doctor for Rp. 100,000 / visit and nurses 75,000 / visit. But in the aspect of home care officers is still inadequate. Home care workers have a dual role between serving the community at the puskesmas, as well as serving the community at the residence. In the process sub-variables, it can be quite good. In the call center aspect, people can easily call the call center because this service is toll free. Home visits and observations have been carried out carefully. But the division of duties of home care officers is not optimal. In the output sub-variable, it can be said to be good because the public can directly benefit from home care services.